The Silent Extinction: Sign Languages with No Native Users Left - Mohit Saini (Universitas Sebelas Maret, 2026)
Sign languages, like spoken languages, face the threat of extinction when their native users disappear. This paper examines the silent extinction of sign languages (SLs) that have lost their last native users, focusing on cases such as Old Kentish Sign Language and Martha’s Vineyard Sign Language. These SLs vanished due to factors like standardization, cultural assimilation, and lack of documentation, leaving gaps in our understanding of Deaf history and linguistic diversity. Unlike well-documented sign languages such as ASL or BSL, extinct SLs often leave behind only fragmentary evidence, such as historical texts or community anecdotes. This study explores the causes of their disappearance, the challenges in reconstructing them, and the ethical implications of reviving or preserving these lost languages. The research calls for greater recognition of extinct SLs as part of humanity’s intangible cultural heritage and proposes collaborative efforts between linguists and Deaf communities.